Relationship of reticulocyte hemoglobin equivalent (Ret- He) to the different categories according to hemoglobin concentration in blood donor applicants. - Aro, Aro (2023)
Objective: to determine the relationship between Ret-He with different categories according to hemoglobin concentration in candidates for blood donation. Methods: A cross-sectional study was carried out based on the review of 227 medical records of candidates to donate blood during the month of December 2021 in the Blood Bank and Hemotherapy Service of the Cayetano Heredia Hospital. They were categorized into 3 groups according to hemoglobin levels: Group 1: ≥12.5 g/ dl (females) - ≥13.5 g/dl (males). Group 2: 12 g/dl ≥ females <12.5 g/dl and 13 g/dl ≥ males<13.5 g/dl. Group 3: <12 g/dl (females) - <13 g/dl (males). Hematocrit, hemoglobin, VCM, HCM, CHCM and Ret-He data were collected. For the bivariate analysis, analysis of variance (ANOVA) was used and a significance level of 5% was considered. Results: The median Ret-He was higher in group 1 than in group 2 (33.5 vs. 32.5; p=0.002) and in group 3 (33.5 vs. 27.8; p<0.001). A statistically significant relationship was found between the groups studied and Ret-He (p<0.001), in addition to a moderate-strong positive correlation between Ret-He and erythrocyte indices. Conclusions: An association was found between groups based on hemoglobin categories and Ret-He in blood donation candidates.